2011
DOI: 10.1002/pssb.201100201
|View full text |Cite
|
Sign up to set email alerts
|

Growth of aligned multi‐walled carbon nanotubes: First in situ and time‐resolved X‐ray diffraction analysis

Abstract: International audienceCatalytic chemical vapour deposition has become a method of choice to produce carbon nanotubes (CNT), particularly for the synthesis of aligned nanotube forests. But a thorough understanding of the mechanisms for CNT nucleation, growth and alignment is still missing. In situ and time resolved experiments allowing to study these processes in real conditions are required. We have developed a specific reactor and furnace to perform such experiments using X-ray diffraction (XRD). Experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Nanotube growth occurs at 1123 K (Pinault et al, 2005) during the injection of aerosol (the conditions are described in detail elsewhere; Landois et al, 2011). As shown in Fig.…”
Section: Typical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanotube growth occurs at 1123 K (Pinault et al, 2005) during the injection of aerosol (the conditions are described in detail elsewhere; Landois et al, 2011). As shown in Fig.…”
Section: Typical Resultsmentioning
confidence: 99%
“…To the best of our knowledge, although in situ XRD studies of CNT growth have already been reported in the literature, the present experiment is the first time-resolved in situ study. It will thus bring new results concerning open questions in the field, such as the nature of the catalyst particles (Landois et al, 2011).…”
Section: Typical Resultsmentioning
confidence: 99%
“…However, such oxide phases are not the catalytic phases in the process we use, where nanoparticles giving rise to CNT growth were shown to be cementite nanoparticles [22]. We have shown that the occurrence of oxides is due to iron oxidation during the cooling step [15], and the present results indicate that the oxidation is not complete for all iron-based particles since Fe 3 O 4 is detected.…”
Section: Methodsmentioning
confidence: 59%
“…In addition, in our study no oxygen-containing promoters such as traces of water have been added to the reactive gas phase. Catalyst particles are formed in-situ in the gas phase from ferrocene decomposition initiating quasi instantaneously the decomposition of toluene and liberating hydrogen in the gas-phase, thus preventing any oxidation of the different phases during CNT growth even with oxygen contamination, as shown through our in-situ study [22]. This is, therefore, not comparable to studies involving catalyst films predeposited on substrates which could be oxidized during annealing through oxygen contamination [32,33].…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation